FUNDAMENTALS OF DISCOURSE FORMATION - Babaeva Gulnozaxon Latibjonovna (Galaxy International Interdisciplinary Research Journal, 2021)
In this article, discourse is considered as a concept that allows for two different pronunciations of the word. It has been argued that discourse serves to illuminate the process of communication in a variety of professions to date.